Can the Chinese connection speed India's development? - Bhoothalingam, Ravi (2015)
China and India are the world's second largest and third largest economies, respectively. Yet, the engagement between their economies remains modest at best and people-to-people contact is minuscule. Will the various Silk Roads proposed by China including the Bangladesh-China- India-Myanmar Economic Corridor and the Maritime Silk Road offer India benefi cial ways to engage with China and the world? How could Sino-Indian economic connectivity help India in achieving its goals of rapid, equitable, balanced, and sustainable development? This essay outlines how the complementary capabilities of India and China can unleash innovation and creativity in both countries, addressing common people's concerns as well as rejuvenating the economies of countries in the neighbourhood. - Reproduced.
Keywords: Economic and social development - India; Economic and social development